(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article aims to present the problem of hospital debt, which has remained atafairlyconstant level for years. It discusses some of the factors causing debt in hospitals operating in the form of independentpublic health service facilities. It also presents the state’s actions towards helping hospitals regain liquidity and improving their financial situation, as well as the legal regulations which provide indebted hospitals with a chance to have their debts remitted and receive subsidies designated for this purpose.